Description of Lobster Catching in The Baai Island Area, Bengkulu City - Rafif Iqra Gunawan; Dedy Bakhtiar; Nurlaila Ervina H (Jurnal Kelautan dan Perikanan Indonesia, 2023)
The waters of the city of Bengkulu, as one of the sources of livelihood for Baii Island fishermen, are located at position 03”47”30” South Latitude and 120”15”40” East Longitude, and have clusters of coral reefs according to the position and name of the coral reefs. Taping 1, Taping 2, Karang Sawang, Karang Lebar, Karang Gosong and other coral reefs are the destinations for fishermen to catch lobsters. Based on the results of field research on 3 fishing boats that catch lobsters using gill nets, obtained results; 11 stone prawns (Panulirus penicillatus) (36.70%) with carapace length between 11.2 – 16.7 cm, weight between 110 – 470 grams. Sand Shrimp (Panulirus homarus) 8 heads (26.70%), carapace length between 13.5 – 15.9 cm, weight between 200 – 300 grams. Pearl Shrimp (Panulirus ornatus), 5 individuals (16.60%) with carapace length between 15.6 – 17.7 cm, weight between 280 – 590 grams, and Bamboo Shrimp (Panulirus polyhagus) 6 individuals (20.00%) with carapace length between 12.9 – 18.7 cm, weight between 260 – 630 grams. From the results of the regression analysis using the formula, W = a Lb, it is known that b 3. Thus, the relationship between carapace length and weight is negative allometric, with the understanding that carapace length growth is not directly/significantly proportional to weight growth. Or in other words, the growth of carapace length is faster than the growth of lobster weight.Keywords: Gill net, lobster, Bengkulu city lobster fishermen